Perioperative hair removal in the 21st century: utilizing an innovative vacuum-assisted technology to safely expedite hair removal before surgery. - Edmiston, Charles E.; Griggs, Russell K.; Tanner, Judith; Spencer, Maureen; Seabrook, Gary R.; Leaper, David (Elsevier, 2016)
Background: Perioperative hair removal using clippers requires lengthy cleanup to remove loose hairs contaminating the operative field. We compared the amount of hair debris and associated microbiologic contamination produced during clipping of surgical sites using standard surgical clippers (SSC) or clippers fitted with a vacuum-assisted hair collection device (SCVAD). Methods: Trained nurses conducted bilateral hair clipping of the chest and groin of 18 male subjects using SSC or SCVAD. Before and during clipping, measurements of particulate matter and bacterial contamination were evaluated on settling plates placed next to each subject’s chest and groin. Skin condition after clipping and total clipping/cleanup times were compared between SSC and SCVAD. Results: The microbial burden recovered from residual hair during cleanup in the SSC group was 3.9 log10 CFU and 4.6 log10 CFU from respective, chest, and groin areas. Use of the SCVAD resulted in a significant (P < .001) reduction in both residual hair and microbial contamination within the operative field compared with SSC. Conclusions: Use of SCVAD resulted in significant (P< .001) reduction in total time required to clip and clean up residual hair contaminating the operative field compared with standard practice (ie, SSC), eliminating the need to physically remove dispersed hairs, which can harbor a significant microbial burden, from within the operative field.